Monoclonal antibody treatment exposes three mechanisms underlying the clinical course of multiple sclerosis. - Coles, A; Wing, MG; Molyneux, P; Paolillo, A; Davie, C; Hale, G; Miller, D; Waldmann, H; Compston, A (1999)
The elective treatment of patients with multiple sclerosis, using a humanized anti-leukocyte (CD52) monoclonal antibody (Campath-1H), has illuminated mechanisms that underlie the clinical course of the disease. Twenty-seven patients were studied clinically and by magnetic resonance imaging (MRI) before and for 18 months after a single pulse of Campath-1H. The first dose of monoclonal antibody was associated with a transient rehearsal of previous symptoms caused by the release of mediators that impede conduction at previously demyelinated sites; this effect remained despite selective blockade of tumor necrosis factor-alpha. Disease activity persisted for several weeks after treatment but thereafter radiological markers of cerebral inflammation were suppressed for at least 18 months during which there were no new symptoms or signs. However, about half the patients experienced progressive disability and increasing brain atrophy, attributable on the basis of MRI spectroscopy to axonal degeneration, which correlated with the extent of cerebral inflammation in the pretreatment phase. These data support the formulation that inflammation and demyelination are responsible for relapses of multiple sclerosis; that inflammatory mediators, but not tumor necrosis factor-alpha, cause symptomatic reactivation of previously demyelinated lesions; and that axonal degeneration, conditioned by prior inflammation but proceeding despite its suppression, contributes to the progressive phase of disability. These results provide evidence supporting the emerging view that treatment in multiple sclerosis must be given early in the course, before the consequences of inflammation are irretrievably established.